The effect of upper limb casting on gait pattern. Issue 2 (June 2016) - Dreyfuss, Daniel; Elbaz, Avi; Mor, Amit; Segal, Ganit; Calif, Edward
Abstract : Casting of the arm may interfere with normal walking patterns because of additional load of the cast or prevention of arm swing. This study aimed to determine the effect of applying various casts on temporospatial walking parameters, including gait velocity and cadence, step length, and single limb support. A computerized gait system was used to assess these variables for 23 healthy individuals in four walking modes: normal walking, with a cast above the elbow and a sling, and with a cast below the elbow, with and without a sling. Thirteen participants had their dominant hand casted and 10 had their nondominant hand casted. On average, casted participants took significantly smaller steps with the leg on the casted side and spent less time supported on the casted side. The least changes were noted with the arm in a cast below the elbow and no sling, and the greatest changes were noted with the arm in a cast above the elbow and in a sling. This difference was heightened when the dominant hand was casted and lessened when the nondominant hand was casted. No differences were found in walking velocity or cadence between the walking modes. Casting of the upper limb has significant effects on gait, which should be taken into consideration, especially in individuals with previous gait abnormalities.